Thermodynamic parameters of the chromatographic equilibrium distribution process of amphiphilic compound by HPLC. Part II: Nonylphenol Polyethoxylated - Bravo, Bélgica; Chávez, Gerson; Cáceres, Ana; Ysambertt, Fredy; Márquez, Nelson (Ciencia, 1970)
The oligomer distribution of polyethoxylated surfactants was determined by isocratic normal-phase HPLC on amino column at variable column temperature. As temperature increases, both the absolute retention and selectivity decrease, with a resulting decrease in the separation of the individual oligomers. The effect is correlated with the rising lipophilic character of surfactant species as temperature increases, hence decreasing the interaction with the polar stationary phase. Therefore, the resolution and elution time of the surfactant oligomers can be adjusted by simply changing the temperature. HPLC experiments carried out at different temperatures allow to obtained Van”™t Hoff plot, and to calculate the free energy (DG°), enthalpy (DH°) and entropy (DS°) of transfer of one oligomer molecule from the mobile phase to the stationary phase.